A strong salt-resistant self-degradable plugging agent for water-based drilling fluid and preparation method thereof

Through the preparation method of strong anti-salt self-degradation sealing agent for water-based drilling fluid, the melt blending technology of modified polyhydroxy fatty acid ester and quaternized lignin is used to solve the problems of unstable sealing and insufficient salt resistance during drilling, and the effect of effective sealing and self-degradation is achieved to ensure the stability of the well wall and reservoir protection.

CN118995157BActive Publication Date: 2025-02-28SOUTHWEST PETROLEUM UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411490545.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-02-28
Estimated Expiration
2044-10-24

AI Technical Summary

Technical Problem

The prior art is difficult to effectively seal micron-scale cracks in the shale formation during drilling, and conventional sealant is unstable in high temperature and high pressure environments, making it difficult to avoid complex underground accidents. At the same time, its salt resistance is insufficient, resulting in unsatisfactory sealing effect.

Method used

A strong anti-salt self-degradation sealing agent for water-based drilling fluid is prepared by melt blending of modified polyhydroxy fatty acid esters and quaternized lignin. It has good biocompatibility and degradability, and can degrade itself after stably sealing the formation cracks.

Benefits of technology

The degradation rate of this sealant is less than 15% within 7 days, which can effectively block micron-scale cracks in the shale formation, maintain the stability of the well wall, protect the reservoir, and have excellent salt resistance to avoid the occurrence of complex underground accidents.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

The present invention provides a strong salt-resistant self-degradable plugging agent for water-based drilling fluid and a preparation method thereof, which belongs to the field of oilfield chemistry. The preparation method of the present invention includes: using 2-acrylamide-2-methylpropanesulfonic acid to modify unsaturated polyhydroxyalkanoate to prepare modified polyhydroxyalkanoate; using ammonium halide to modify lignin to prepare quaternized lignin; quaternized lignin and modified polyhydroxyalkanoate are melt-blended to obtain a strong salt-resistant self-degradable plugging agent for water-based drilling fluid. The preparation method of the present invention is mature and reliable, suitable for industrial production, the plugging agent of the present invention is strong salt-resistant, has good stability, and has a degradation rate of less than 15% in 7 days, and can effectively plug micron-level cracks in shale formations; at the same time, the plugging agent of the present invention can be directly added to the water-based drilling fluid, and has little effect on the rheology of the water-based drilling fluid. After adding the plugging agent, the high-temperature and high-pressure filtration loss of the drilling fluid is significantly reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of oilfield chemistry, in particular to a strong salt-resistant self-degradation plugging agent for water-based drilling fluid and a preparation method thereof. Background Art

[0002] Shale formations have developed micron pores and fractures. During the drilling process, plugging agents with different particle sizes need to be used for graded plugging to ensure the stability of the wellbore. However, conventional polymer plugging agents are difficult to degrade in the natural environment, causing environmental pollution. In addition, their stability in the high temperature and high pressure environment underground is limited, which can easily lead to reservoir damage. Although acidification and fracturing technology can increase the seepage channel, this significantly increases the construction cost. In addition, the conventional organic and inorganic plugging agents have insufficient salt resistance, resulting in unsatisfactory plugging effects, making the drilling fluid loss volume high, and easily causing serious underground complex accidents such as well collapse, stuck drill, and obstruction. Therefore, it is necessary to develop self-degradable plugging materials, which can not only form a dense plug on the wellbore wall and improve the stability of the wellbore wall, but also self-degrade in the later stage of completion, restore the reservoir permeability, and achieve the effect of restoring the fracture conductivity during the completion and production stage.

[0003] At present, polylactic acid, which has a good degradation effect, degrades rapidly under high temperature and easily loses strength, and cannot meet the demand for reservoir section leakage control materials during drilling and completion. For drilling fluid, the ideal self-degradable plugging material is to degrade slowly or not degrade in the early stage to achieve leakage control in the drilling stage, and degrade rapidly and fully in the later stage to reduce damage to the reservoir. According to the performance requirements of oil and gas drilling for self-degradable plugging materials, the degradation rate of self-degradable plugging agents within 7 days needs to be less than 15% to play a role in stably plugging formation cracks and improving the stability of shale well walls. At present, there are some temporary plugging agents prepared from degradable materials, such as the two-dimensional flexible temporary plugging agent for fracturing disclosed in CN118206977A, and the degradable spherical shell knot temporary plugging agent for fracturing disclosed in CN118165715A. They are all used for fracturing construction, and the degradation time is short. They cannot meet the long-term effective plugging of formation cracks and it is difficult to avoid the problem of drilling fluid invading the formation. Summary of the invention

[0004] In order to solve the above problems, the purpose of the present invention is to provide a strong salt-resistant self-degradable plugging agent for water-based drilling fluid and a preparation method thereof. The plugging agent has good stability and is degradable, with a degradation rate of less than 15% within 7 days. It can effectively plug micron-level cracks in shale formations, thereby achieving the purpose of maintaining well wall stability and protecting reservoirs.

[0005] To achieve the above objectives, the technical solution of the present invention is as follows:

[0006] A method for preparing a strong salt-resistant self-degradable plugging agent for water-based drilling fluid comprises the following steps:

[0007] S1, preparing modified polyhydroxyalkanoate, comprising the following steps:

[0008] S11, 6-8 parts by weight of unsaturated polyhydroxyalkanoate, 3-4 parts by weight of 2-acrylamide-2-methylpropanesulfonic acid and 0.1-0.3 parts by weight of a dispersant are uniformly dispersed in deionized water, and an inert gas is introduced to remove oxygen in the solution;

[0009] S12, add 0.05-0.1 parts by weight of an initiator to the mixed solution of S11, raise the temperature to 70°C-90°C and react for 12h-16h;

[0010] S13, naturally cooling and vacuum drying the reaction product of S12 to obtain a modified polyhydroxyalkanoate;

[0011] S2, using ammonium halide to modify lignin to prepare quaternary ammonium lignin;

[0012] S3. The quaternized ammonium lignin and the modified polyhydroxyalkanoate are melt-blended to obtain a strong salt-resistant self-degradable plugging agent for water-based drilling fluid.

[0013] In the present invention, unsaturated polyhydroxyalkanoates refer to polyhydroxyalkanoates containing unsaturated units in the side chains, such as poly (3-hydroxyoctanoate-co-3-hydroxyundecenoate) (PHOU). The side chains of unsaturated polyhydroxyalkanoates have terminal reactive double bonds, are relatively active, and can be chemically modified to introduce new functional groups to form functional polyhydroxyalkanoates.

[0014] The inert gas in the present invention refers to a gas that does not react with each monomer, such as nitrogen, helium, etc.

[0015] As a specific embodiment of the present invention, the dispersant is sodium dodecyl sulfate (SDS) or Tween 80.

[0016] As a specific embodiment of the present invention, the initiator is potassium persulfate or ammonium persulfate.

[0017] As a specific implementation of the present invention, step S2 includes:

[0018] S21, dissolving 7-8 parts by weight of lignin and 3-4 parts by weight of ammonium halide in N,N-dimethylformamide, and adding an alkaline reagent to adjust the pH value to 11-12;

[0019] S22. Stir the mixture of S21 at 70°C~80°C for 18h~24h; after the reaction is completed, the reaction product is rotary evaporated, dialyzed for purification, and freeze-dried at -30°C~-50°C to obtain quaternary ammonium lignin.

[0020] In step S21, the alkaline reagent is a conventional reagent for adjusting pH value, such as K2CO3, NaOH, etc.

[0021] As a specific embodiment of the present invention, the ammonium halide salt is 3-chloro-2-hydroxypropyltrimethylammonium chloride (CHPTAC) or diallyldimethylammonium chloride.

[0022] As a specific embodiment of the present invention, in step S3, the mass ratio of the modified polyhydroxyalkanoate to the quaternized lignin is 1-3.

[0023] As a specific embodiment of the present invention, in step S3, the melt blending temperature is 190°C~200°C, and the specific blending time is also related to the rotation speed, etc., and can be selected as needed. For example, when the rotation speed is 60r / min~65r / min, the blending time is 6min~7min.

[0024] A highly salt-resistant self-degradable plugging agent for water-based drilling fluid is prepared by adopting the method.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] The plugging agent of the present invention has good biocompatibility and degradability, can be self-degraded after stably plugging formation cracks, and does not pollute the formation. The grafted sulfonic acid functional group has strong heat resistance and salt resistance.

[0027] The plugging agent of the present invention contains lignin material, has good degradability and thermal stability, and the quaternary ammonium functional group is adsorbed on the clay particles, so that the plugging agent can be well adsorbed on the stratum surface, thereby improving the compactness of the plugging layer. At the same time, through the hydration of the quaternary ammonium functional group, a solvation layer can be formed on the molecular chain of the plugging agent, and the plugging agent molecules absorb water and expand, thereby improving the plugging ability of the cracks.

[0028] The plugging agent of the present invention has good compatibility with water-based drilling fluid, can effectively prevent the drilling fluid from penetrating into the formation, prevent the occurrence of well collapse accidents, and enhance the stability of the well wall. The preparation method of the present invention is mature and reliable and is suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 a is a scanning electron microscope image of the plugging agent of Example 1 before degradation;

[0030] Figure 1 b is a scanning electron microscope image of the plugging agent after degradation in Example 1;

[0031] Figure 2 The degradation rate of each plugging agent changes with time. DETAILED DESCRIPTION

[0032] The specific implementation modes of the present invention will be described clearly and completely below with reference to examples. Obviously, the examples described are only some embodiments of the present invention, rather than all embodiments.

[0033] In the following examples, poly (3-hydroxyoctanoate-co-3-hydroxyundecenoate) (PHOU) was purchased from Beijing Microstructure Factory Biotechnology Co., Ltd.; lignin and Tween 80 were purchased from Sigma-Aldrich (Shanghai) Trading Co., Ltd.; 2-acrylamide-2-methylpropanesulfonic acid, sodium dodecyl sulfate, potassium persulfate, ammonium persulfate, K2CO3, and NaOH were purchased from Sinopharm Chemical Reagent Company; 3-chloro-2-hydroxypropyltrimethylammonium chloride (CHPTAC) and diallyldimethylammonium chloride were purchased from Aladdin Reagent Company; N,N-dimethylformamide was purchased from Shanghai Jizhi Biochemical Technology Co., Ltd.

[0034] Example 1: S1. Preparation of modified polyhydroxyalkanoate: 6 parts by weight of PHOU, 3 parts by weight of 2-acrylamide-2-methylpropanesulfonic acid and 0.1 parts by weight of sodium dodecyl sulfate were uniformly dispersed in deionized water, nitrogen was introduced and stirred for 1 hour; then 0.05 parts by weight of ammonium persulfate was added to the mixed solution, the temperature was raised to 70° C. and the mixture was reacted for 16 hours; after the reaction was completed, the reaction product was naturally cooled, and then dried under vacuum at 60° C. for 6 hours to obtain a modified polyhydroxyalkanoate;

[0035] S2. Preparation of quaternary ammonium lignin: dissolving 7 parts by weight of lignin and 3 parts by weight of 3-chloro-2-hydroxypropyltrimethylammonium chloride in 200 parts by weight of N,N-dimethylformamide, and adding NaOH solution to adjust the pH value to 11; then stirring the mixture at 70°C for 18 hours; after the reaction is completed, concentrating by rotary evaporation to remove N,N-dimethylformamide, and then dialysis purification and freeze-drying at -30°C for 3 hours to obtain quaternary ammonium lignin.

[0036] S3. Add the modified polyhydroxyalkanoate and quaternized lignin into the torque rheometer in a mass ratio of 3:1, and melt-blend (temperature of 190°C, rotation speed of 60r / min, blending time of 7min) to obtain a strong salt-resistant self-degradable plugging agent.

[0037] Example 2: S1. Modified polyhydroxyalkanoate prepared: 7 parts by weight of PHOU, 3 parts by weight of 2-acrylamide-2-methylpropanesulfonic acid and 0.2 parts by weight of Tween 80 were uniformly dispersed in deionized water, nitrogen was introduced and stirred for 2 hours; then 0.07 parts by weight of potassium persulfate was added to the mixed solution, the temperature was raised to 80° C. and the mixture was reacted for 14 hours; after the reaction was completed, the reaction product was naturally cooled and then dried under vacuum at 70° C. for 5 hours to obtain a modified polyhydroxyalkanoate;

[0038] S2. Preparation of quaternary ammonium lignin: dissolve 7 parts by weight of lignin and 4 parts by weight of diallyldimethylammonium chloride in 200 parts by weight of N,N-dimethylformamide, and add NaOH solution to adjust the pH value to 12; then stir the mixture at 75°C for 22 hours; after the reaction is completed, concentrate by rotary evaporation to remove N,N-dimethylformamide, then dialysis purification and freeze-drying at -40°C for 3 hours to obtain quaternary ammonium lignin.

[0039] S3. Add the modified polyhydroxyalkanoate and quaternized lignin into the torque rheometer in a mass ratio of 2:1, melt blend (temperature of 200°C, rotation speed of 65r / min, blending time of 6min) to obtain a strong salt-resistant self-degradable plugging agent.

[0040] Example 3: S1. Preparation of modified polyhydroxyalkanoate: 8 parts by weight of PHOU, 4 parts by weight of 2-acrylamide-2-methylpropanesulfonic acid and 0.3 parts by weight of sodium dodecyl sulfate were uniformly dispersed in deionized water, nitrogen was introduced and stirred for 1.5 hours; then 0.1 parts by weight of ammonium persulfate was added to the mixed solution, the temperature was raised to 90° C. and the mixture was reacted for 12 hours; after the reaction was completed, the reaction product was naturally cooled, and then dried under vacuum at 80° C. for 4 hours to obtain a modified polyhydroxyalkanoate;

[0041] S2. Preparation of quaternized lignin: 8 parts by weight of lignin and 3 parts by weight of 3-chloro-2-hydroxypropyltrimethylammonium chloride (CHPTAC) are dissolved in 200 parts by weight of N,N-dimethylformamide, and K2CO3 is added to adjust the pH value to 12; the mixture is then stirred at 75°C for 22 hours; after the reaction is completed, the mixture is concentrated by rotary evaporation to remove N,N-dimethylformamide, and then dialyzed and purified and freeze-dried at -40°C for 3 hours to obtain quaternized lignin;

[0042] S3. Add the modified polyhydroxyalkanoate and quaternized lignin into the torque rheometer in a mass ratio of 1:1, melt blend (temperature of 200°C, rotation speed of 65r / min, blending time of 6min) to obtain a strong salt-resistant self-degradable plugging agent.

[0043] Comparative Example 1

[0044] S1. Preparation of quaternary ammonium lignin: 7 parts by weight of lignin and 4 parts by weight of diallyldimethylammonium chloride are dissolved in 200 parts by weight of N,N-dimethylformamide, and K2CO3 is added to adjust the pH value to 11; the mixture is then stirred at 70°C for 24 hours; after the reaction is completed, the mixture is concentrated by rotary evaporation to remove N,N-dimethylformamide, and then purified by dialysis and freeze-dried at -35°C for 3 hours to obtain quaternary ammonium lignin.

[0045] S2. Add polylactic acid and quaternized lignin in a mass ratio of 3:1 into a torque rheometer, melt blend (temperature of 200° C., rotation speed of 65 r / min, blending time of 6 min) to obtain a self-degradable plugging agent.

[0046] In order to further illustrate the effect of the plugging agent of the present invention, performance tests were performed on the plugging agents in Example 1, Example 2, Example 3 and Comparative Example 1.

[0047] Test Example 1 (Scanning electron microscope test before and after plugging agent degradation)

[0048] The plugging agent prepared in Example 1 was placed in a high-temperature roller heating furnace and aged at 120°C for 1 day. The plugging agent before and after aging was subjected to scanning electron microscope microscopic analysis. The microscopic morphology of the plugging agent before aging was observed under a scanning electron microscope. Figure 1 As shown in a, it presents a spherical structure with a smooth surface; the plugging agent after aging is as follows Figure 1 As shown in b, the surface of the particles becomes rough and a large number of white irregular protrusions appear, but the overall shape still maintains a complete spherical structure, indicating that the plugging agent has been degraded.

[0049] Test Example 2 (Self-degradation Performance Test of Plugging Agent)

[0050] The plugging agents of Examples 1 to 3 and Comparative Example 1 were respectively placed in a high-temperature roller heating furnace and aged at 120° C. The degradation rates after different aging times were measured, and the degradation characteristics of the plugging agents were measured by the degradation rates.

[0051] The degradation rate calculation formula is:

[0052] S =( W 1- W 2) / W 1×100%

[0053] In the formula, S is the degradation rate; W 1 is the mass of the plugging agent before aging; W 2 is the remaining mass of the plugging agent after aging.

[0054] The test results are as follows Figure 2 As shown, the plugging agents of Examples 1 to 3 degrade slowly, with degradation rates less than 15% within 7 days, which can better meet the needs of crack plugging and reservoir protection; the plugging agent of Comparative Example 1 degrades quickly, and the degradation rate after 24 hours is greater than 20%, and it cannot stably plug formation cracks for a long time during drilling.

[0055] Test Example 3 (Test of the Salt Resistance Performance of the Plugging Agent)

[0056] The original particle sizes of the plugging agents prepared in Examples 1 to 3 and Comparative Example 1 were tested respectively, and then the four plugging agents were added to sodium chloride NaCl solutions with a mass percentage of 15%, 20%, 25%, and 30%, respectively, stirred evenly, and allowed to stand at room temperature for 1 day, and the particle sizes were tested respectively to obtain the median particle size D of the plugging agents at different NaCl salt concentrations. 50 As shown in Table 1, with the increase of the concentration of NaCl solution, the median particle size of the plugging agents of Examples 1-3 changes slightly and is always maintained at 1 μm~3 μm, indicating that they have excellent salt resistance. After adding 15% by mass salt solution, the median particle size of the plugging agent of Comparative Example 1 increases from 2.05 μm to 6.52 μm, and with the increase of the concentration of NaCl solution, the particle size increases significantly. It can be seen that there is agglomeration effect to varying degrees under the stimulation of salt solution, and the salt resistance is worse than that of Examples 1 to 3.

[0057] Table 1 Median particle size D at different NaCl salt concentrations 50 (μm)

[0058]

[0059] Test Example 4 (Compatibility test of plugging agent and water-based drilling fluid)

[0060] Prepare water-based drilling fluid base slurry: by weight, add 100 parts of water, 3 parts of bentonite, and 0.2 parts of NaOH solid to a high-stirring cup and stir for 10 minutes; under high-stirring state, weigh 0.02 parts of coating agent potassium polyacrylate (KPAM) and add it to the high-stirring cup, and stir for 10 minutes; then add 5 parts of sulfomethylphenolic resin (SMP-Ⅰ), 5 parts of anti-collapse agent FRH, 4 parts of anti-seizure lubricant FK-10, 0.4 parts of alkalinity regulator CaO, and 2 parts of shearing agent. Each time a substance is added, stir at high speed for 10 minutes; finally, slowly add 22 parts of barite to the high-stirring cup and continue stirring for 30 minutes.

[0061] Take multiple parts of water-based drilling fluid slurry with the same weight, add different weight parts of plugging agents of Examples 1 to 3 and Comparative Example 1 respectively (the amount of plugging agent added is based on the weight of the water-based drilling fluid slurry), and obtain water-based drilling fluids containing different mass contents and different types of plugging agents. At the same time, a water-based drilling fluid without plugging agent, i.e., slurry, is set as a blank experimental group. Each water-based drilling fluid is aged at 150°C for 16 hours, and its performance parameters are measured respectively. The results are shown in Table 2.

[0062] Table 2 Performance parameters of water-based drilling fluids formed by different amounts of plugging agents

[0063]

[0064] Note: The temperature of HTHP is 150℃ and the pressure is 3.5MPa.

[0065] As shown in Table 2, with the increase of the amount of plugging agent, the apparent viscosity and plastic viscosity of the water-based drilling fluid slowly increase, and the high temperature and high pressure fluid loss (HTHP) decreases with the increase of the amount of plugging agent, and the fluid loss decreases significantly. When the amount of plugging agent exceeds 1.5%, the fluid loss of Examples 1 to 3 is maintained between 4.1 mL and 5.0 mL, indicating that the plugging agent has good rheological properties and water loss wall building properties, and can effectively reduce the high temperature and high pressure fluid loss of the drilling fluid, and can provide good plugging performance even in a high temperature environment, effectively preventing the filtrate from entering the formation and improving the stability of the well wall. The high temperature and high pressure fluid loss of the water-based drilling fluid added with Comparative Example 1 is relatively high, which is due to the significant degradation and rapid degradation rate, resulting in the inability to effectively plug the formation cracks.

[0066] The present invention has been disclosed in the above preferred embodiments, but those skilled in the art should understand that these embodiments are only used to describe the present invention and should not be construed as limiting the scope of the present invention. Further improvements can be made without departing from the principles of the present invention, and these improvements should also be included in the protection scope of the present invention.

Claims

1. A method for preparing a strong salt-resistant self-degradable plugging agent for water-based drilling fluid, characterized in that: The steps include: S1, preparing modified polyhydroxyalkanoate, comprising the following steps: S11, 6-8 parts by weight of unsaturated polyhydroxyalkanoate, 3-4 parts by weight of 2-acrylamide-2-methylpropanesulfonic acid and 0.1-0.3 parts by weight of a dispersant are uniformly dispersed in deionized water, and an inert gas is introduced to remove oxygen in the solution; S12, add 0.05-0.1 parts by weight of an initiator to the mixed solution of S11, raise the temperature to 70°C-90°C and react for 12h-16h; S13, naturally cooling and vacuum drying the reaction product of S12 to obtain a modified polyhydroxyalkanoate; S2, using ammonium halide to modify lignin to prepare quaternary ammonium lignin; S3, melt-blending the quaternized lignin and the modified polyhydroxyalkanoate to obtain a strong salt-resistant self-degradable plugging agent for water-based drilling fluid; The unsaturated polyhydroxyalkanoate is poly(3-hydroxyoctanoate-co-3-hydroxyundecenoate); The ammonium halide salt is 3-chloro-2-hydroxypropyltrimethylammonium chloride or diallyldimethylammonium chloride.

2. The method for preparing a strong salt-resistant self-degradable plugging agent for water-based drilling fluid according to claim 1, characterized in that: The dispersant is sodium dodecyl sulfate or Tween 80.

3. The method for preparing a strong salt-resistant self-degradable plugging agent for water-based drilling fluid according to claim 1, characterized in that: The initiator is potassium persulfate or ammonium persulfate.

4. The method for preparing a strong salt-resistant self-degradable plugging agent for water-based drilling fluid according to claim 1, characterized in that: Step S2 includes: S21, dissolving 7 to 8 parts by weight of lignin and 3 to 4 parts by weight of ammonium halide in N,N-dimethylformamide, and adding an alkaline reagent to adjust the pH value to 11 to 12; S22. Stir the mixture of S21 at 70°C~80°C for 18h~24h; after the reaction is completed, the reaction product is rotary evaporated, dialyzed for purification, and freeze-dried at -30°C~-50°C to obtain quaternary ammonium lignin.

5. The method for preparing a strong salt-resistant self-degradable plugging agent for water-based drilling fluid according to claim 1, characterized in that: In step S3, the mass ratio of the modified polyhydroxyalkanoate to the quaternized lignin is 1-3.

6. The method for preparing a strong salt-resistant self-degradable plugging agent for water-based drilling fluid according to claim 1, characterized in that: In step S3, the temperature of the melt blending is 190°C to 200°C.

7. A strong salt-resistant self-degradable plugging agent for water-based drilling fluid, characterized in that: The invention is prepared by the method for preparing the strong salt-resistant self-degradation plugging agent for water-based drilling fluid according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Degradable spherical shell type knot temporary plugging agent for fracturing and preparation method thereof

    CN118165715A

  • Two-dimensional flexible temporary plugging agent for fracturing and preparation method thereof

    CN118206977A

  • Intelligent blocking water-based drilling fluid

    CN105018051A

  • Method for microwave auxiliary synthesis of quaternized lignin in low-concentration alkali lye

    CN106916320A